2021
DOI: 10.3390/cancers13143548
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Mechanisms Associating Alcohol Use Disorders with Cancers

Abstract: The World Health Organization identifies alcohol as a cause of several neoplasias of the oropharynx cavity, esophagus, gastrointestinal tract, larynx, liver, or female breast. We review ethanol’s nonoxidative and oxidative metabolism and one-carbon metabolism that encompasses both redox and transfer reactions that influence crucial cell proliferation machinery. Ethanol favors the uncontrolled production and action of free radicals, which interfere with the maintenance of essential cellular functions. We focus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 335 publications
(503 reference statements)
0
8
0
Order By: Relevance
“…Excessive consumption can cause neuropathological symptoms [ 67 ], cardiovascular diseases [ 68 ], liver diseases [ 69 ], intestinal diseases [ 70 ], liver cancers [ 71 ], and infectious diseases due to the weakened immune system of the body [ 72 ]. The main component of alcoholic drinks is ethanol, which has shown to exert oxidative damages to biological macromolecules via acetaldehyde-DNA/RNA/protein adduct formation, thereby drastically inducing cellular ROS production and systemic OS [ 14 , 19 , 22 ]. These toxic conditions can then lead to abrupt changes in the levels of antioxidant enzymes and other forms of antioxidant molecules in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive consumption can cause neuropathological symptoms [ 67 ], cardiovascular diseases [ 68 ], liver diseases [ 69 ], intestinal diseases [ 70 ], liver cancers [ 71 ], and infectious diseases due to the weakened immune system of the body [ 72 ]. The main component of alcoholic drinks is ethanol, which has shown to exert oxidative damages to biological macromolecules via acetaldehyde-DNA/RNA/protein adduct formation, thereby drastically inducing cellular ROS production and systemic OS [ 14 , 19 , 22 ]. These toxic conditions can then lead to abrupt changes in the levels of antioxidant enzymes and other forms of antioxidant molecules in the body.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic functions of CYP2E1 and ADH reportedly produce RNS and ROS, which in turn activate downstream enzymes such as nitric oxide synthase, nicotinamide adenine dinucleotide phosphate (NADP) oxidase, and xanthine oxidase [ 17 ]. Furthermore, acetaldehyde consumes reduced glutathione (GSH), perturbing the intracellular redox balance, resulting in oxidative stress (OS) [ 22 ]. Therefore, alcohol and its toxic metabolites may be the sole cause of increased cellular burdens of ROS/RNS and other types of highly reactive free radicals and superoxides, leading to the OS injuries to the vital organs of the body [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary exposures have been shown to interact with each other and resultant biology linked with cancer. Mechanisms for alcohol-induced carcinogenesis suggest that one-carbon (folate) metabolism may play an important role 42 , and the formation of aldehydes and ROS that promote carcinogenesis by covalently modifying DNA, proteins, and lipids resulting in altered function 43,44 . Interestingly, alcohol consumption was shown to increase blood beta-carotene levels, likely due to interference by ethanol in its conversion to vitamin A even at moderate alcohol intake, potentially promoting carcinogenesis 45 .…”
Section: Association Between Amn and Lifestyle Factorsmentioning
confidence: 99%
“…In addition, lipoperoxidation products non-enzymatically react with proteins through Michael additions and Schiff base formation and generate lipid and DNA adducts. [ 110 ]. HNE has been linked to site-specific mutations of the p53 gene [ 111 ].…”
Section: Toxicity Of Ethanolmentioning
confidence: 99%
“…At the same time, unrepaired DNA adducts propagate as mutations after DNA replication. [ 110 ]. Recently, Guidolin et al [ 118 ] identified by DNA adductomic approach 22 DNA adducts in DNA exposed to acetaldehyde, and adduct levels were observed to generally increase with acetaldehyde concentration for all the detected modifications.…”
Section: Toxicity Of Ethanolmentioning
confidence: 99%